Microfluidics - The State-of-the-Art Technology for Pharmaceutical Application - Anisha Verma; Sayani Bhattacharyya (Tabriz University of Medical Sciences, 2022)
Microfluidics (MF) is the science dealing with the behavior, precise control, and manipulation of fluids as well as particles on the scale of tens to hundreds of micrometers. It is also utilized for chemical and biological applications, usually called micro-total analysis systems (µTAS) or lab-on-a-chip (LOC). MF is a fascinating and capable technology with various superior benefits compared to conventional macro-scale platforms, such as the lesser requirement of sample and reagent volumes, higher sensitivity, low cost, portability, faster processing of samples and potential to be automated and highly integrated to reduce human errors. The concept of transformation of meso to nanoliters using MF technology has shown its potential in the healthcare system for early diagnosis, and personalized medicine. The integrated multifunctional system with parallelization provides a better and faster process control. Minimization of the consumption of fluid makes the technology safer in every aspect of the development process, analysis, and storage. The impressive improvement in patient care and monitoring has led to the commercial motivation of the pharmaceutical industry to develop new drugs and modify existing products with better efficacy and safety in a cost-effective manner using MF technologies. Hence, the present review briefs on the applications of MF technology in the key issues of the drug discovery process, overcoming the limitations of development of analytical procedures and prosperous pharmaceutical manufacturing for novel controlled and targeted release dosage forms to fabricate quality products.